Dual modulation of the morphology and electric conductivity of NiCoP on nickel foam by Fe doping as a superior stability electrode for high energy supercapacitors. Issue 41 (14th October 2021) - Chang, Xinwei; Liu, Tingting; Li, Weilong; He, Mi; Ren, Zhaoyu; Bai, Jintao
Abstract : The dual advantages of stable morphology and enhanced electric conductivity of NiCoP by Fe doping endow the optimal Fe–NiCoP/NF-12.5% electrode with prominent cycling stability and rate performance. Abstract : Nickel–cobalt bimetallic phosphide (NiCoP) is a potential electrode material for supercapacitors on account of its high theoretical specific capacitance. However, its practical application is restricted because of its relatively poor cycling stability and rate performance. Herein, we constructed self-standing NiCoP nanowires and Fe doped NiCoP nanoarrays with different iron ion concentrations on nickel foam (Fe–NiCoP/NF- x %, x = 4, 6.25, 12.5, 25) as a positive electrode for asymmetric supercapacitors (ASCs). The morphological result reveals that the nanostructure of the material evolves from nanowires to nanosheets with the iron doping concentration, and the Fe–NiCoP/NF-12.5% nanosheets possess a more stable structure than NiCoP/NF nanowires. The density functional theory analysis implies that the conductivity of the material enhances after Fe doping because of the increased charge density and electron states. The combination of multicomponents and structural advantages endows the optimal Fe–NiCoP/NF-12.5% electrode with an ultrahigh areal capacitance of 9.93 F cm −2 (2758.34 F cm −3 ) under 1 mA cm −2, excellent rate capability (82.58% from 1 mA cm −2 to 50 mA cm −2 ) and superior cycling stability (95.72% retention over 5000 cycles under 20 mA cm −2 ), and the areal capacitance of Fe–NiCoP/NF-12.5% is 2.27 times higher than that of the pristine NiCoP/NF electrode at 1 mA cm −2 . Moreover, the assembled Fe–NiCoP/NF-12.5%//activated carbon ASC device delivers a high energy density of 0.327 mW h cm −2 (60.43 mW h cm −3 ) at 1.10 mW cm −2 (202.54 mW cm −3 ). Therefore, this strategy may provide a novel route for the application of NiCoP with its intrinsic advantages in the energy storage field.